2008
DOI: 10.1111/j.1525-1446.2008.00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Satisfaction Levels of Japanese Volunteers in Meal Delivery Services for the Elderly

Abstract: Satisfaction levels of volunteers in meal delivery services for the elderly were most affected by human relations with fellow volunteers, meal service users, and professional staff members. Increasing opportunities for communication may be important to promote good human relationships among volunteers and volunteer activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…However, this could be skewed by the double-counting of Japanese workers who have two or more employers in the OECD statistics 18. The characteristics of healthcare systems do not explain divergent national practices regarding home-delivered meals, perhaps because this service is often provided by welfare services instead, as in Japan 19. Moreover, in Japan, meal preparation can also be part of the duties of paid home helpers.…”
Section: Discussionmentioning
confidence: 99%
“…However, this could be skewed by the double-counting of Japanese workers who have two or more employers in the OECD statistics 18. The characteristics of healthcare systems do not explain divergent national practices regarding home-delivered meals, perhaps because this service is often provided by welfare services instead, as in Japan 19. Moreover, in Japan, meal preparation can also be part of the duties of paid home helpers.…”
Section: Discussionmentioning
confidence: 99%
“…Volunteering can also help maintain good mental health and foster a greater sense of community, especially within the elderly population (Warburton and Winterton 2017). Past research has shown that good relationships with other volunteers and staff were correlated with greater satisfaction of volunteer work (Yanagisawa and Sakakibara 2008). Mirosa et al (2016) study of volunteers in a food rescue social enterprise in New Zealand also highlighted the value of social benefits (alongside altruistic emotional benefits) for volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…31 Thus, it is possible to highlight the importance of interpersonal relationships for the volunteer workers which allow the creation of meaningful connections. But volunteer work goes beyond these interpersonal relationships, enabling individuals to acquire knowledge and reflect on their values and the world they inhabit, allowing new relationships to develop.…”
Section: [] the Volunteers Who I Met We Ended Up Developing A Frimentioning
confidence: 99%
“…Thus, working with this public implies a respect for the characteristics of children with cancer, who focus on the present moment, as they deal with illness in a positive way most of the time 31 For the toy library volunteers, learning goes beyond the physical and psychological characteristics of the child. There is also the possibility of expanding knowledge in various areas of knowledge, in addition to developing new skills.…”
mentioning
confidence: 99%